EVOLUCION DE LA SIQUIATRIA Y GENESIS DEL SIQUIATRA - Nizama V., Martín (2024)
A brief historie revision Is made for the evolution of psychiatrist role, since the antique age until the present time, with the purpose of recovering its professional image, to define its social scientific action, to project its real professional lmage, to relieve lt,; identity with the psychiatric occupation and to affirm its leadership In the mental health area. Since year 313 aJ.C. up to 1793, the psycbiatrists were marginated in the attention ofpsychiatric patients, dueto the supernatural conceptlon of the mental illness that prevailed during the medieval time. Since then the psychiatry and the psychlatrists have lnherited stigmas that still prevail in the social consensus. Sorne trascendental contributlons to the psychiatric field by paradigmatic figures of the medicine and of the universal psychlatry are mentioned. At last, the high grade of scientific, academic and humanistic formation of modero psychlatrist is described, which qualifies as a psychoterapists and mental health promoters by antonomasia.